Electrocardiographic and Echocardiographic Profile of Dilated Cardiomyopathy Patients (Cardiovascular Journal, 2020)
Background: Cardiomyopathy is a primary disorder of heart muscle with abnormal myocardial performance. It is an important cause of heart failure and accounts for upto 25% of causes of heart failure. In view of the high prevalence of chronic heart failure due to underlying dilated cardiomyopathy and the lack of data on DCM, the study was undertaken.Methods: A total of 100 patients (71 males and 29 females) of dilated cardiomyopathy were taken who was undergone Echocardiography at popular Diagnostic centre, Rangpur. ECG and echocardiography was done among all these patients using standard techniques.Results: Majority of the patient was above the age 50 years with male to female ratio is 2.4 :1. Sinus tachycardia, non specific ST-T change, LVH, non progression of R in v1-v5 were common ECG abnormalities.Conclusion: ECG may be normal in patients with DCM though sinus tachycardia and non specific ST-T abnormalities were common.Cardiovasc. j. 2020; 12(2): 109-112